2015
DOI: 10.14237/ebl.6.1.2015.451
|View full text |Cite
|
Sign up to set email alerts
|

“Buying a Pig in a Poke”: The Problem of Elasmobranch Meat Consumption in Southern Brazil

Abstract: In Brazil, the demand for sustainably certified seafood is increasing and retailers have promised to source all seafood from sustainable sources by 2015. In the southern portion of the country, elasmobranch meat is sold as cação, and consumers are often unaware that cação refers to any type of elasmobranch. The present study used questionnaires to investigate the lay public’s knowledge of elasmobranch meat sold in a Brazilian city. Shoppers were surveyed at supermarkets in Curitiba, the largest city in souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
0
31
0
2
Order By: Relevance
“…Even though the species are the same, the former does not have the stigmatized name and is more widely accepted as food ( Bornatowski, Braga & Vitule, 2013 ). What is puzzling is that more than half of the population believes they are different animals ( Bornatowski et al, 2015 ). Moreover, in Brazil there is no control that requires the identification of Shark species by commercial establishments and it is usually sold only with the generic term of “Cação” as we have shown in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the species are the same, the former does not have the stigmatized name and is more widely accepted as food ( Bornatowski, Braga & Vitule, 2013 ). What is puzzling is that more than half of the population believes they are different animals ( Bornatowski et al, 2015 ). Moreover, in Brazil there is no control that requires the identification of Shark species by commercial establishments and it is usually sold only with the generic term of “Cação” as we have shown in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that Brazilians do not know they are eating sharks. In a large city in southern Brazil, more than 70% of surveyed consumers were unaware that "cação" refers to sharks, and more than half of the respondents claimed to have already eaten "cação" but have never eaten sharks or rays [10].…”
Section: Trade and Consumptionmentioning
confidence: 99%
“…At the same time that its fishing management collapsed, the country became the first global shark meat importer according to FAO [25]. While domestic production is unknown [49], information on how Brazilians use sharks is poor [9,10]. In this light, the objective of the present study is to show how Brazil has contributed substantially to the consolidation of the truly global market for shark products established over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the world's largest consumers of elasmobranchs include Brazil and Uruguay, accounting for 20,992 and 4,077 captures between 2000 and 2011, respectively (Dulvy et al, 2014). This consumption includes threatened species, such as several elasmobranchs locally named "cação" (Bornatowski, Braga, Kalinowski, & Vitule, 2015), which most people do not realize that refers to sharks and rays.…”
Section: Fisheriesmentioning
confidence: 99%